Nafkah Wanita Karier dalam Pespektif Fikih Klasik - B. Syafuri (Universitas Islam Negeri Jakarta, 2013)
Abstract: Support Payments of Career Woman within the Perspective of Classical Fiqh. This article attempts to research the right to support payments of career woman or woman in work. In traditional classic fiqh, the husband is liable to provide for support payments to his wife based on the principle of separation of property between husband and wife. This principle follows a flow of thought that a husband earns money instead of the wife. The understanding of the working wife or career woman which must be made dependent to the husband’s permission needs to be re-examined or reviewed because the scholars have not mentioned the obvious arguments concerning the matter. Likewise, no proposition exists which prohibits, either men or women, to work as well as no firm proposition about the need to have the husband’s permission to go to work. Similarly, many historical facts reveal that there were working women or career women in the time of the Prophet, such as ‘A’ishah, Ummu Mubâshir, and others.Keywords: support payments (living support), career woman, nushûzAbstrak: Nafkah Wanita Karier dalam Pespektif Fikih Klasik. Artikel ini mencoba meneliti tentang hak nafkah wanita karier atau perempuan yang bekerja. Dalam tradisi fikih klasik, suami berkewajiban memberikan nafkah kepada istrinya didasarkan pada prinsip pemisahan harta antara suami dan istri. Prinsip ini mengikuti alur pikir bahwa suami adalah pencari rezeki, sedangkan istri bukan pencari rezeki. Pemahaman istri bekerja atau wanita karier yang harus digantungkan kepada izin suami itu perlu dibaca ulang atau ditinjau kembali karena ulama tidak menyebutkan dalil yang jelas tentang hal itu. Dan juga tidak adanya dalil yang melarang, baik laki-laki maupun perempuan, untuk bekerja serta tidak ada dalil yang tegas tentang keharusan bekerja dengan izin suami. Begitu juga banyaknya fakta sejarah yang mengungkapkan wanita-wanita yang bekerja atau wanita karier di masa Nabi, seperti ‘Â’ishah, Ummu Mubâshir, dan lain-lain.Kata Kunci: nafkah, wanita karier, nusyu (nushûz)DOI: 10.15408/ajis.v13i2.933